Air Rebusan Daun Akasia Menurunkan Kadar Glukosa Darah Penderita Diabetes Melitus - Yunike Yunike; Ira Kusumawaty; Ferawaty Suzalin; Tedi Tedi (Journal of Telenursing (JOTING), 2023)
This study looks at the intervention of giving acacia leaf boiled water to reduce blood glucose levels. The case study method collected data directly on respondents using interviews, observation sheets, and direction glucose measurements. The results showed a decrease in blood glucose levels before and after being given acacia leaf boiled water for three days. In conclusion, education related to diabetes mellitus and complementary therapy are given together with the provision of interventions, and an increase in the knowledge, skills, and attitudes of the participants is obtained. Keywords: Acacia Leaves, Diabetes Mellitus, Blood Glucose, Polyphenols